THE USE OF ANIMATION VIDEO AS A MEDIUM IN TEACHING VOCABULARY TO FOURTH GRADERS OF SDN 04 OKU - Diffa Kamila; Nopa Yusnilita; Neti Lastri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2024)
The researcher conducted a study entitled “The Use of Animation Video as a Medium in Teaching Vocabulary to Fourth Graders of SDN 04 OKU.” The study aimed to determine the effectiveness of using animation videos in teaching vocabulary. A pre-experimental research design was applied, with a sample of 20 fourth-grade students from class 4D at SDN 04 OKU. The instruments used included multiple-choice and matching tests comprising 30 questions. The data were analyzed using a paired sample T-test. The results showed a significant improvement from a pre-test score of 62.00 to a post-test score of 93.5. The statistical significance value (Sig = 0.000) indicated that the animation video had a significant effect on students’ vocabulary acquisition. The study concluded that animation video is an effective medium for improving vocabulary among elementary school students.